Advancements In Immunotoxicology Research: A Comprehensive Review - Jamakala, Obaiah; B, Padmaja; Rani, K Usha; Kumari, P Prasanna; Matha, Vijaya Santhi; Ramakrishna, M; Chintada, Vivek (Journal of Neonatal Surgery, 2025)
Immunotoxicology is a critical field that delves into the effects of environmental factors and chemicals on the immune system. Recent progress in this area has shed light on the mechanisms underlying immune-related disorders and diseases. However, a comprehensive review is essential to consolidate the latest findings and methodologies, bridging existing gaps to advance our understanding further. The goal of this review is to present a thorough overview of the recent breakthroughs in immunotoxicology research, emphasizing significant discoveries and emerging trends. By synthesizing this information, we aim to provide a comprehensive perspective on the current landscape of the field and its potential implications for human health. Key highlights of this review address various aspects of immunotoxicology such as the influence of environmental factors on immune function, innovative approaches to toxicity testing, and advancements in predictive modeling of immune responses. Through an exploration of the latest findings in immunotoxicology, this review seeks to educate researchers, professionals, and policymakers on using these advancements to enhance human health outcomes and tackle immune-related challenges effectively.